Development a tool to evaluate the effectiveness of the participatory methodologies used in rural development - Kaushalya, B. L. C. (My University, 2009)
Participatory methodologies are highly practiced in community development activities. Absence of a proper methodology to evaluate the effectiveness and efficiency of participatory methodologies conducted by government and semi-government projects causes wastage of monetary, human and other resources of a project. General objective of this study is to develop a tool to evaluate the participatory methodologies used in community development and as specific objectives are to identify the different kinds of participatory methodologies used in community development and to identify the major differences in the participatory process conducted by government and semi- government sector in Sri Lanka and developing a common framework. Methods such as primary data collection, secondary data collection, focus group discussion, general discussions, specialist discussions and stake holder discussions were conducted in order to develop the evaluation tool. It consists of an ideal participatory methodology assessment frame work developed including variables and means of verifications and three sub components. The selected two projects were Gamanaguma Program conducted in Godayagama village (Meegahakiwla Divisional Secretariat) and Gemidiriya Project conducted in Imbulgoda village (Hali-Ela Divisional Secretariat).Total amount of the respondents of this study was 60 beneficiaries and 10 project field level coordinators. The Primary data was collected through two questionnaires and discussions. …